Importância da sinalização de Anexina A1 no estabelecimento da agressividade do câncer de mama - Zóia, Mariana Alves Pereira (2015)
CHAPTER II: Annexin A1 (ANXA1) protein role in breast cancer (BC) has not been well elucidated since contradictory reports suggest both tumor-promoting and tumor-suppression activities. We analyzed ANXA1 expression, localization and signaling through FPR receptors in BC cell lines and in normal breast cell line (MCF-10A). ANXA1 is highly expressed, massively secreted and intensively localized in the nuclear compartment in MDA-MB-231 triple negative BC cell line (TNBC). ANXA1 secretion in MDA-MB-231 cells is accompanied by FPR1 expression, through which, ANXA1 activates PI3K/Akt and MAP kinases (MAPK) signaling pathways. By using human BC tissue samples we also confirmed that ANXA1 is predominantly expressed in TNBCs and its expression associates with lymph node metastasis. Subsequently, we demonstrated that ANXA1/FPR1 signaling induced an increase in endogenous ANXA1 translocation to the nuclear compartment, which was dependent on PI3K activation and correlated with increased MDA-MB-231 aggressiveness. Furthermore, we demonstrated that ANXA1 signaling leads to IL-2 secretion which, in turns, through its autocrine signaling in MDA-MB-231, contributes to PI3K/Akt axis activation. Since PI3K activity is essential for MDA-MB231 migration, IL-2 is apparently one of the pivotal molecules involved in TNBC cells migration. Finally, we demonstrated that FPR1 signaling trans-activates the epidermal growth factor receptor (EGFR) leading to MAPK cascade activation and MDA-MB-231 cells survival. The association between ANXA1 and EGFR expression was also demonstrated in human BC tissue samples. Altogether, our results shed light on the crucial role of ANXA1/FPR1 signaling in TNBCs aggressiveness emphasizing the possibility of inhibiting ANXA1 signaling for amelioration of breast cancer management.